STONE VATS (KALAMBAS) AS ONE OF MEGALITHIC REMAINS IN THE LORE VALLEY, CENTRAL SULAWESI - Umar, Dwi Yani Yuniawati (Berkala Arkeologi, 2010)
The province of Central Sulawesi, particulariy Lore Valley that is part of Poso Regency, is rich in cultural remains from the period when the megalithic tradition flourished. The remains include among others kalamba (stone vats), megalithic statues, stone mortars, pitted stones, engraved stones, and clay jars. The Lore Valley area consists of Bada, Besoa, and Napu smaller valleys. Here, there are scatter of very specific cultural items rarely found in other parts of Indonesia, which are locally known as kalamba (stone vats). Stone vats are usually functioned as burial containers. Excavations reveals that stone vats were communal and secondary burials. C-14 dating shows that one of the sites at Besoa Valley, Entovera Site, has been inhabited since 2170 BP. This makes Entovera Site one of the oldest megalithic sites in Indonesia. Outside Central Sulawesi, megalithic burials resemble to kalamba are found in Sarawak, North around Lake Toba (North Sumatra), Donggo, (West Nusa Tenggara), Mekong Valley (Laos), and Assam (to the northwest of Cachar Mountains in India).